2003
DOI: 10.1039/b201317g
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and the hydrogenases

Abstract: The reversible reduction protons to dihydrogen: 2H+ + 2e [symbol: see text] H2 is deceptively the simplest of reactions but one that requires multistep catalysis to proceed at practical rates. How the metal-sulfur clusters of the hydrogenases catalyse this interconversion is currently the subject of extensive structural, spectroscopic and mechanistic studies of the enzymes, of synthetic assemblies and of in silico models. This is driven both by curiosity and by the view that an understanding of the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
372
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 601 publications
(384 citation statements)
references
References 52 publications
6
372
2
3
Order By: Relevance
“…The noble metal, Pt, shows perfect activity for HER, however it is expensive and scarcity on earth. Meanwhile some natural enzymes which contains much less noble metals are also effective HER catalysts 33, 34. By comparing the active center of nitrogenase with different inorganic compounds, the Nørskov group found that the MoS 2 edge possess similar structure and was chosen as a candidate for HER 35.…”
Section: Edges As Active Sitesmentioning
confidence: 99%
“…The noble metal, Pt, shows perfect activity for HER, however it is expensive and scarcity on earth. Meanwhile some natural enzymes which contains much less noble metals are also effective HER catalysts 33, 34. By comparing the active center of nitrogenase with different inorganic compounds, the Nørskov group found that the MoS 2 edge possess similar structure and was chosen as a candidate for HER 35.…”
Section: Edges As Active Sitesmentioning
confidence: 99%
“…2,3 Since the elucidation of the structures of both [NiFe]-and [FeFe]-hydrogenases revealed that these enzymes feature organometallic active sites including the diatomic ligands CO and CN (Figure 1), [4][5][6][7] inorganic chemists have sought to produce both structural and functional models in an effort to understand and reproduce these enzymes. 8 However, although natural hydrogenases have turnover frequencies exceeding 1000 s -1 at potentials close to the thermodynamic reduction potential of the proton, synthetic models seldom come close to this exquisite reactivity. 9,10 The active site of [FeFe]-hydrogenases, referred to as the H-cluster, is a unique six iron cluster consisting of a [4Fe4S] cluster bridged via a cysteinyl thiolate to a diiron subsite.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in this area have afforded molecular electrocatalysts that employ cobalt, molybdenum, nickel, or iron [6][7][8][9][10][11], instead of platinum that is currently the preferred electrocatalyst for proton reduction in water [12]. Given the interest of developing H 2 -production electrocatalysts based on cheap and abundant materials, synthetic models of the iron-iron hydrogenase enzymes have been the subject of numerous studies [13][14][15][16][17][18]. Diiron-dithiolate compounds of the type [Fe 2 (µ-SRS)(CO) 6-x L x ] (R = organic group, L = electron-donor ligand, x ≤ 4) have been shown to electrocatalyze the reduction of acid in organic solvents [19][20][21] and, very recently, in aqueous micellar solutions [22,23](for examples of photo-driven H 2 -production by diiron-dithiolate compounds see [24,25]).…”
Section: Introductionmentioning
confidence: 99%